Menepis Hoax Melalui Pendidikan Karakter dan Pembelajaran Sastra - Sri Widayati (Universitas Muhammadiyah Kotabumi, 2019)
Hoax is one of social media evil. It is not only happen on adult, but also on children. Hoax brings negative effect for society, especially for children because they will have a bad behavior. So to solve this problem, they need character education. Character education is one of education to improve values of nation characters on students. Character education will be successful with litration culture, that is literature learning. The students will face directly about live value of figures, such as religion value, honestly, tolerance, love, justice, and service. By internalization that value, hopely the students will avoid from hoax activities.